2019
DOI: 10.3389/fchem.2019.00296
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Homogeneous (Cyclo)Isomerization Reactions

Abstract: Gold is currently one of the most used metals in organometallic catalysis. The ability of gold to activate unsaturated groups in different modes, together with its tolerance to a wide range of functional groups and reaction conditions, turns gold-based complexes into efficient and highly sought after catalysts. Natural products and relevant compounds with biological and pharmaceutical activity are often characterized by complex molecular structures. (Cyclo)isomerization reactions are often a useful strategy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 142 publications
0
30
0
Order By: Relevance
“…Toste's group (Sethofer et al, 2010) also reported gold(I)-catalyzed enantioselective cascade cyclization for construction of diverse fused scaffolds. These works then added fuel to the gold-catalyzed reactions (Gorin and Toste, 2007;Hashmi, 2007;Li et al, 2008) to stimulate rapid development of cascade cyclization via goldcatalyzed alkyne activation in the past decade (Fensterbank and Malacria, 2014;Zhang et al, 2014;Dorel and Echavarren, 2015;Pflästerer and Hashmi, 2016;García-Morales and Echavarren, 2018;Marín-Luna et al, 2019).…”
Section: Construction Of Polycyclic Carbocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Toste's group (Sethofer et al, 2010) also reported gold(I)-catalyzed enantioselective cascade cyclization for construction of diverse fused scaffolds. These works then added fuel to the gold-catalyzed reactions (Gorin and Toste, 2007;Hashmi, 2007;Li et al, 2008) to stimulate rapid development of cascade cyclization via goldcatalyzed alkyne activation in the past decade (Fensterbank and Malacria, 2014;Zhang et al, 2014;Dorel and Echavarren, 2015;Pflästerer and Hashmi, 2016;García-Morales and Echavarren, 2018;Marín-Luna et al, 2019).…”
Section: Construction Of Polycyclic Carbocyclesmentioning
confidence: 99%
“…Multiple reactive sites or components may interact on each other, making it difficult to balance the reactivity and selectivity for several successive steps in one pot. In the past two decades, we have witnessed blossoming of new synthetic toolkits including C-H functionalization (Chen and Youn, 2012;Yamaguchi et al, 2012;Gulías and Mascareñas, 2016;Abrams et al, 2018;Sambiagio et al, 2018;Zheng and Hua, 2018;Ghosh et al, 2020), palladium catalysis (Chinchilla and Najera, 2014;Düfert and Werz, 2016;Trost and Min, 2020), and gold catalysis (Fürstner, 2009;Zhang et al, 2014;Dorel and Echavarren, 2015;Pflästerer and Hashmi, 2016;Marín-Luna et al, 2019). These emerging synthetic methodologies enable new cascade reaction in mild conditions via substrate activation (for alkynes, their reaction partners, or both of them), thus expanding the utilization of alkynes for syntheses of polyheterocycles with higher efficiency and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Since the rise of homogeneous gold catalysis in the first decade of the century, cycloisomerizations have been one of the major class of reactions to be studied in details. [76][77][78] Those reactions are of infinite richness in terms of structural complexity since they combine in general two unsaturated arms. In a number of reactions, the late stage of the mechanistic pattern involves the formation of a carbocation that can be trapped by a nucleophile.…”
Section: Reactions Involving Indoles As An External Nucleophilementioning
confidence: 99%
“…A reduction of the number of steps in the synthesis of complex compounds can be attained by cascade reactions, which allow for structural modifi-cations on the organic compounds by forming several chemical bonds in one pot. To this end, gold catalysis [1][2][3][4][5][6][7] has been widely exploited to construct various cyclic and heterocyclic frameworks through cascade reactions triggered by the activa- tion of a triple bond, which has ultimately led to the total synthesis of several natural compounds [2,8]. The gold-catalyzed rearrangement of suitably substituted propargylic esters in particular provides a platform for cascade processes that involve a cationic or an allene intermediate generated in the first step [1,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, gold catalysis [ 1 – 7 ] has been widely exploited to construct various cyclic and heterocyclic frameworks through cascade reactions triggered by the activation of a triple bond, which has ultimately led to the total synthesis of several natural compounds [ 2 , 8 ]. The gold-catalyzed rearrangement of suitably substituted propargylic esters in particular provides a platform for cascade processes that involve a cationic or an allene intermediate generated in the first step [ 1 , 9 12 ].…”
Section: Introductionmentioning
confidence: 99%